2007
DOI: 10.1088/1742-6596/61/1/089
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Growth of Human Fibroblasts on Silver Nanoparticles

Abstract: Silver nanoparticles have drawn extensive attention as biomaterial components. Human fibroblasts were grown on various concentrations of silver nanoparticles during the period observation. Normal viability (0% silver particles) was increased from 6 to 72 hours, increasing the amount of human fibroblasts (1.5x10 4 to 7x10 6 cells/well) normally. Nevertheless, at higher concentrations of silver nanoparticles (50%) 1.11x10 5 cells/well remained after 72 hours. Results indicated that the increase in the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…Similar mechanism has been quoted for silver ions and nano particles [125]. Silver nano-particles are a non-toxic and non-tolerant disinfectant [128][129][130]. Using silver nano-particles leads to increase in number of particles per unit area and, thus, anti-bacterial effects can be maximized [131].…”
Section: Silver Nano-particlesmentioning
confidence: 62%
See 1 more Smart Citation
“…Similar mechanism has been quoted for silver ions and nano particles [125]. Silver nano-particles are a non-toxic and non-tolerant disinfectant [128][129][130]. Using silver nano-particles leads to increase in number of particles per unit area and, thus, anti-bacterial effects can be maximized [131].…”
Section: Silver Nano-particlesmentioning
confidence: 62%
“…Some examples can be pointed out as follows: Skin-innoxiousness of nano-silver colloidal solution especially in the case of smaller nano-particles has been demonstrated via the skin irritation test performed on the rabbits [140]. Nontoxicity of the interaction of nano-silver and the membrane surface has been proved by growing human fibroblasts on various concentrations of silver nano-particles [128]. Silver is mentioned as an almost non-toxic to mammalian systems [317] Incubation of astrocyte primary cultures with magnetic iron oxide nano-particles has also demonstrated that the particles do not induce any acute damage to these brain cells [316].…”
Section: Potentiality Of Health and Environmental Risks Of Nano-strucmentioning
confidence: 99%
“…Although the actual mechanism of AgNps functioning is not yet clear, researchers believe that AgNps interact with thiol group of bacterial proteins (Lok et al, 2006) and phosphorous moieties of DNA (Rai et al, 2009) to inactivate the bacterial cell system. It was also reported that nano-silver is non-toxic to humans at low doses (Wen et al, 2007; Tankhiwale and Bajpai, 2009). Thereafter, few attempts were made to develop AgNps coated systems, especially for food preservation against lethal food borne pathogens.…”
Section: Introductionmentioning
confidence: 98%
“…36 Interaction of AgNPs with human fibroblasts affected their fission, but it was not toxic. 37 Though AgNPs are reported to cause no big health problems when administered into the body, argyria is always a problem, irrespective of the nanosize of silver. 38 In daily life, AgNPs-impregnated clothing may find a good applicability in underwear and socks.…”
mentioning
confidence: 99%